Spatial variation of the total ozone column in Huancayo, Santiago de Chile and Antarctica during 2005-2020 - Angeles Suazo, Julio Miguel (2022)
The objective of this research is to determine the variation of the total ozone column over the regions of Huancayo, Santiago de Chile and Antarctica. The study focused on measurements of the total ozone column over Huancayo, Santiago de Chile and the Machupicchu Antarctic Research Station (ECAMP). Total column ozone data were obtained by NASA's Ozone Monitoring Instrument (OMI) over 16 years (2005-2020). Likewise, it was obtained that in Huancayo a monthly average of 243.1 Dobson Units (DU). In the Peruvian Antarctic station there is a monthly average of 276 DU. And, finally, the registered data obtained the minimum and maximum value of 237 (May) and 254 (September) respectively. Likewise, in Santiago de Chile the minimum and maximum value of 251 (March) and 301 (September) respectively were obtained. In Antarctica, the minimum and maximum value of 220 (September) and 310 (December) respectively were obtained.